Financial Inclusion and Income Inequality in Asia: A Quantile Panel Analysis - Linda Rosalina; Wisnu Wibowo (Journal of Developing Economies, 2025)
Objective: This empirical study investigates the heterogeneous impact of financial inclusion on income inequality across the economically and institutionally diverse Asian region. Specifically, it examines how the effect of financial inclusion varies across different segments (quantiles) of the inequality distribution, a dimension largely unexplored by prior research. Methods: Utilizing an annual panel dataset spanning 29 Asian countries from 2010 to 2022, the study employs the Panel Quantile Fixed Effect model. This robust econometric approach is selected to effectively control for unobserved country-specific heterogeneity and to address the non-normal, outlier-prone nature typical of income inequality data. Analysis is focused on the lower (Q10), median (Q50), and upper (Q90) quantiles. Findings: Estimation results consistently demonstrate that financial inclusion significantly reduces income inequality across all tested quantiles (Q10 ,Q50, Q90), with statistical significance maintained across the board (e.g., Q10: p=0.031, : Q90:p=0.059). The most substantial mitigating impact is identified at the median quantile (Q50), exhibiting a large negative coefficient of -4.9404 (p=0.000). This key finding suggests that FI is most effective in countries characterized by moderate levels of inequality. Among the control variables, trade openness significantly exacerbates inequality at the Q50 level, while other macroeconomic factors are generally insignificant. Originality: The primary novelty lies in the application of the Panel Quantile Fixed Effect method to a broad 29-country Asian sample to precisely capture FI’s differentiated impact. By providing nuanced, quantile-specific estimations, this research significantly advances beyond conventional mean-based studies (such as OLS and GMM), confirming that financial inclusion’s role in inequality reduction is heterogeneous and conditional on a country’s initial inequality level. Policy implication: These findings underscore the critical need for adaptive, non-uniform financial inclusion policies. Policymakers in Asia must tailor their financial inclusion strategies—including the types of services offered—based on the specific level of inequality they currently confront. This targeted approach is essential to maximizing the effectiveness of financial inclusion in promoting sustainable income equality.